Auditory sensory processing induces cortical and thalamic event-related desynchronization in the mouse - Sarah H. McGill; Qilong Xin; Taruna Yadav; Charlie W. Zhao; Patrick Paszkowski; Fabrizio Darby; Mrinmoyee Guha; Tramy Nguyen; David S. Jin; Yuval Nir; Jiayang Liu; Lim-Anna Sieu; et al. (PLoS ONE, 2025)
Studies of human perception have shown early cortical signals for primary information encoding, and later signals for higher order processing. An important late signal is the cortical event-related desynchronization (ERD) in the alpha (8–12 Hz) and beta (12–30 Hz) frequency band, which has been linked to human perceptual awareness. Detailed mechanistic investigation of the ERD would be greatly facilitated by availability of a suitable animal model. We conducted local field potential recordings in the mouse frontal association cortex (FrA), thalamic intralaminar centrolateral nucleus (CL), primary auditory cortex (A1), and primary visual cortex (V1) during two auditory tasks. Fully audible brief 50 ms stimuli with both tasks produced early broadband gamma (30–100 Hz) frequency activity at 0–250ms, followed by a late cortical alpha/beta ERD 250–750 ms after stimulus onset. The ERD was statistically significant in FrA and A1, but not in V1. Interestingly, a significant ERD was also observed in thalamic CL. The magnitude of the ERD at full stimulus intensity, and the slope of the relationship between stimulus intensity versus ERD magnitude, were both largest in FrA, and smaller in CL and A1. Conversely, for early broadband gamma activity the magnitude at full intensity and slopes were largest in A1, smaller in CL and smaller still in FrA. These findings strongly support mice as a promising platform for further investigation of the ERD to better understand the origin and function of this robust yet understudied electrophysiological phenomenon.